USING RCRR (READ, COVER, REMEMBER, AND RETELL) IN ENHANCING THE FIRST GRADE STUDENTS' READING COMPREHENSION ABILITY - Rahayu, Yayu Sri; Widiastuti, Rizki; Kusnandar, Agus (SIMPLE: International Journal of English Education, 2024)
Students in second grade at SMP Karya Pembangunan  Baros Bandung, a private school in Bandung, should be able to comprehend descriptive text based on the 2013 English syllabus curriculum. The researchers used Read Cover, Remember Retell (RCRR) to teach descriptive text reading comprehension to first-grade students at SMP KP Baros Bandung Junior High School. This study aimed to compare the impact of the Read Cover, Remember Retell (RCRR) approach on reading comprehension and recall of text among students taught without it. This research used a quasi-experimental method. The population consisted of 60 first-grade pupils from SMP KP Baros Bandung. The research sample comprised 30 students from VIIA (experimental) and 30 from VIIB (control). Data was collected through reading tests, pre-tests, and post-tests. Data analysis techniques include T-tests, U-Mann Whitney, and N-gain. The study indicated that the experimental class had a higher n-gain average score (0.425) than the control class's 0.315. The experimental class showed greater improvement than the control class. In conclusion, the Read Cover, Remember Retell (RCRR) technique improves students' reading comprehension of second-grade descriptive material at SMP KP Baros Bandung.